The Road to Collaborative Governance in China
XI, 241 p. 16 illus.
Keywords: Faced with unprecedented socioeconomic changes, China has increasingly embraced collaborative governance (CG), the sharing of power and discretion between and within public, private, and nonprofit sectors for public purposes. This book analyzes new areas of CG development such as environmental protection, disaster response, and infrastructure.